Chronic mania: A case series - Priyanka Hooda; Bhupendra Khobragade; Ananya Mahapatra; Shipra Singh (Annals of Indian Psychiatry, 2023)
Chronic mania is a known but underexplored entity and still lacks nosological status. Earlier reports of chronic mania have found distinct symptomatology, course, outcome, and treatment challenges. Three cases of chronic mania are presented with challenges in treatment, variable response to drugs and different outcomes along with a synopsis of review of literature in this context. There is a need for longitudinal follow-up studies of patients with diagnosis suggestive of chronic mania for better understanding of treatment response and outcome.